Monitoring Viscosity of Polymer Products on the Reactor Tank Using IoT-based NodeMCU - Paduloh, Paduloh (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2023)
Viscosity is one of the critical parameters for polymer products; thus, monitoring the viscosity level is very important to know during the production process and production results. The Polymer Company recently suffered heavy losses due to an explosion in one of its reactor engines, the R306 engine. The investigation results show that the viscosity of the polymer is one of the causes of the heavy workload of the machine, when the viscosity is checked manually. This research was conducted based on these conditions, and a viscosity monitoring device was designed for the 306-tank product. The design used QFD visualization for product design and UML for information system design. In this study, polymer viscosity was measured using the falling ball method with an Infrared Sensor E18-D80NK to obtain the viscosity of polymer products. Viscosity data are configured directly with the Internet of Things using the NodeMCU microcontroller. The design results show that the tool can monitor the viscosity in the tank and provide polymer viscosity information in real-time, thus facilitating decision-making and increasing productivity.